The Wearable Band with Electromagnetic Band Gap Antenna for Heart Rate Detection System - Sitepu, Karolina; Hafizha, Syahna; Riansyah, Aldi; Salim, Akhmad Raihan; Prabowo, Vinsensius Sigit Widhi; Nur, Levy Olivia; Ryanu, Harfan Hian (JMECS (Journal of Measurements, Electronics, Communications, and Systems), 2024)
Wearable antennas are antennas that can be applied to the human body and are made of flexible materials, making them ideal for healthcare technology. The quality of the signal received by the antenna directly affects the accuracy of heart rate detection If the antenna measurements indicate strong, clear signal reception, the heart rate monitor can accurately detect and interpret heartbeats. In this study, a planar monopole antenna was designed and developed using a circular patch with Ultra Wide Band (UWB) characteristics. The FR-4 and copper were utilized for the substrate and the ground plane and patch, respectively. Simulations and measurements were conducted at 2.4 GHz and 5 GHz. The antenna with the added EBG structure showed improved performance compared to the conventional antenna, exhibiting better S11 and VSWR values. Additionally, all radiation patterns were unidirectional.  Applying this antenna to transmit heart rate measurements results in an accuracy of  94.34% compared to conventional onsite heart rate measurement. This study demonstrates that the wearable band provides real-time heart rate monitoring, while the EBG antenna enhances sensitivity and accuracy in detecting heart rate. This research can be enhanced by optimizing the EBG design and conducting additional trials to ensure the device performs well for a variety of users.